Analisis Fenomena Lepas Pasang Hijab Pada Siswa SMA Islam Athirah 1 Makassar Melalui Pendekatan Teori Dramaturgi - Yusran (Journal of Mandalika Literature, 2024)
Appearance is currently in the spotlight of every individual caused by high social and economic changes. Students are one of the actors who experience this change. The hijab is a sacred thing to wear for Muslim women, but in its development the presence of the hijab has become one of the fashions used by students to keep up with the times. This has led to the emergence of the phenomenon of removing the hijab among students, so that dramaturgical theory will analyze the existence of this phenomenon. This research will use qualitative research methods with observation, interview and documentation data collection techniques.